Conjugative Transfer of a Novel Staphylococcal Plasmid Encoding the Biocide Resistance Gene, qacA - LaBreck, Patrick T.; Rice, Gregory K.; Paskey, Adrian C.; Elassal, Emad M.; Cer, Regina Z.; Law, Natasha N.; Schlett, Carey D.; Bennett, Jason W.; Millar, Eugene V.; Ellis, Michael W.; Hamilton, Theron; Bishop-Lilly, Kimberly A.; et al. (Frontiers in Microbiology, 2018)
Staphylococcus aureus is the leading cause of skin and soft tissue infections (SSTI). Some S. aureus strains harbor plasmids that carry genes that affect resistance to biocides. Among these genes, qacA encodes the QacA Multidrug Efflux Pump that imparts decreased susceptibility to chlorhexidine, a biocide used ubiquitously in healthcare facilities. Furthermore, chlorhexidine has been considered as a S. aureus decolonization strategy in community settings. We previously conducted a chlorhexidine-based SSTI prevention trial among Ft. Benning Army trainees. Analysis of a clinical isolate (C02) from that trial identified a novel qacA-positive plasmid, pC02. Prior characterization of qacA-containing plasmids is limited and conjugative transfer of those plasmids has not been demonstrated. Given the implications of increased biocide resistance, herein we characterized pC02. In silico analysis identified genes typically associated with conjugative plasmids. Moreover, pC02 was efficiently transferred to numerous S. aureus strains and to Staphylococcus epidermidis. We screened additional qacA-positive S. aureus clinical isolates and pC02 was present in 27% of those strains; other unique qacA-harboring plasmids were also identified. Ten strains were subjected to whole genome sequencing. Sequence analysis combined with plasmid screening studies suggest that qacA-containing strains are transmitted among military personnel at Ft. Benning and that strains carrying qacA are associated with SSTIs within this population. The identification of a novel mechanism of qacA conjugative transfer among Staphylococcal strains suggests a possible future increase in the prevalence of antiseptic tolerant bacterial strains, and an increase in the rate of infections in settings where these agents are commonly used.